Evaluation of the teacher profile based on the attributes of teaching performance (Revista Innova Educación, 2021)
The purpose of this research was to determine if the levels of teaching performance allow measuring the institutional profile based on a competency approach, as well as knowing its attributes and at what level teachers apply it: theoretically or practically. For this purpose, quantitative, cross-sectional, and correlational research was carried based on the application of two Likert-type questionnaires, obtaining these results: identification of attributes of the institutional teaching profile: mediator, planner, cultural agent, and promoter. It was distinguished that the self-evaluations measured the theoretical application of the teaching profile and the praxis from the evaluations, confirming that both are necessary to achieve the desired teaching profile. Also, the study hypothesis was verified by corroborating that the levels of teaching performance allow measuring the level of institutional teaching profile. In conclusion, the study showed that the teaching profile was satisfactory in the French Bachelor context because the teachers applied the four attributes on a scale from 80 to 89.
Keywords: Teaching performance; competency-based approach; evaluation; teaching profile